Excitatory synaptic transmission between interneurons and motoneurons in chick spinal cord cell cultures - O'Brien, RJ (J Neurosci, 1986)
We have examined the development of synaptic transmission between interneurons and motoneurons in spinal cord cell cultures. Unitary excitatory synaptic currents and complex bursts of excitatory currents develop rapidly: EPSCs (excitatory postsynaptic currents) were detected in 100% of the motoneurons by the 4th day after plating. Inhibitory synaptic currents develop more slowly: IPSCs (inhibitory postsynaptic currents) were detected in only 10% of the motoneurons on day 5 and 40% on day 8. During the 1st and 2nd days in vitro, 24% of the motoneurons tested were dye (Lucifer Yellow) coupled to nearby interneurons. The incidence of dye coupling declined during the first week in culture. No coupling was observed between motoneurons. Our data imply that both G1 and G2 receptors are activated at each synapse. The amplitude of spontaneous excitatory synaptic currents did not change when the motoneuron was hyperpolarized from -50 to -80 mV. This behavior is similar to that of currents induced by glutamate, an agonist that activates 2 types of receptors (G1 and G2) on motoneurons. In addition, a concentration of 2-amino-5-phosphonovaleric acid sufficient to inhibit all G1 receptors only partially inhibited the excitatory synaptic currents. Given the conductance of G1 and G2 channels and the ratio of channels activated during unitary EPSCs, we estimate that as few as 25 G1 channels and 5 G2 channels may mediate excitatory interaction between interneurons and motoneurons during the first week in culture.